Otto Fenichel and Hanna Fenichel papers - Fenichel, Otto.; Fenichel, Hanna
Correspondence, circular letters, minutes, reports, writings, and other papers primarily concerning Otto Fenichel's work as a psychoanalyst and his involvement in psychoanalytic organizations following his immigration to the United States in 1938. Includes copies of his circular letters, Rundbriefe, pertaining to Fenichel's work, especially as a training analyst in Oslo, Norway, and Prague, Czechoslovakia. Subjects include the American Psychoanalytic Association and other psychoanalytic groups, especially in the Middle West and California. Correspondents include Ernest Jones, Anna Maenchen, Karl A. Menninger, Theodor Reik, and Ernst Simmel.
Otto Fenichel (1897-1946), psychoanalyst and author. Hanna Heilborn, lay analyst, married Fenichel in 1940.
Collection material in English and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Sigmund Freud collection.
A portion of the Otto Fenichel and Hanna Fenichel papers formerly cataloged as part of the Sigmund Freud papers, Series Z, was transferred to the Otto Fenichel and Hanna Fenichel papers in 1987.
Hanna Fenichel and K.R. Eissler correspondence formerly cataloged under Hanna Fenichel papers as part of the Miscellaneous Manuscripts collection, was transferred to the Otto Fenichel and Hanna Fenichel papers in 1987.
Keywords: Jones, Ernest, -- 1879-1958 -- Correspondence; Maenchen, Anna -- Correspondence; Menninger, Karl A. -- 1893-1990 -- Correspondence; Reik, Theodor, -- 1888-1969 -- Correspondence; Simmel, Ernst, -- 1882-1947 -- Correspondence; American Psychoanalytic Association; Psychoanalysis -- California -- Societies, etc; Psychoanalysis -- Czech Republic -- Prague; Psychoanalysis -- Middle West -- Societies, etc; Psychoanalysis -- Norway -- Oslo; Psychoanalysis -- United States; Psychoanalysis -- United States -- Societies, etc; Authors; Lay analysts; Psychoanalysts